The Effect of Spraying Rocket Plant Extract and Ground Addition of Organic Nutrient (Karma maxi org) on The Growth and Production of Cabbage - Hussein, Ahlam A. (Diyala Agricultural Sciences Journal, 2021)
The experiment was carried out in open field of the research station at College of Agriculture / University of Diyala during two seasons 2018 and 2019. The aim of the study is to investigate the effect of foliar spraying with water extract of Rocket at three concentrations of 0, 50, and 100% in and ground addition of Organic solution at three concentrations 0, 15, 20 ml. L-1 in. The Randomized Complete Block Design was used with three replicates. The results showed that spraying water extract of Rocket was superior in 100%. It was found that the highest values in stem height, number of external leaves, head diameter and head weight, and total yield for both seasons 13.36 cm, 12.57 leaf, 14.94 cm, 1.302 kg. plant-1 and 43.417 tons. H -1 For the first season, 10.92 cm, 12.64 leaves, 15.26 cm, 1.308 kg. Plant-1 and 43.618 tons. H-1) for the second season. Also, the ground addition of solution was superior at 20 ml. L-1 in all studied traits. They did not differ significantly from the 15ml.L-1 concentration. However, they differ significantly from the control treatment, which gave the lowest values for all traits and both seasons. As for the treatment of interaction which was (20 ml.L-1 and 100% of Rocket extract), it exceeded all treatments and for both seasons.were recorded 13.42 cm, 12.88 leaf, 15.77 cm, 1.351 kg. Plant-1 and 45.028 tons. H-1 for the first season, as well as 11.03 cm, 13.01 leaf, 15.80 cm, 1.383 kg. plant-1 and 46.096 tons. H-1 for the second season